Phylogeny and genetic structure of the goitered gazelle (Artiodactyla, Bovidae) in north-western China indicated by the hypervariable mitochondrial control region. Issue 6 (18th August 2018) - Abduriyim, Shamshidin; Zibibulla, Guzalnur; Eli, Subinur; Ismayil, Zorigul; Halik, Mahmut
Abstract : The goitered gazelle, Gazella subgutturosa, is a medium-sized ungulate inhabiting arid and semi-arid regions in the Middle East and central Asia. The intraspecific classification of the species remains unclear. We analysed the genetic diversity in mitochondrial DNA control region (CR) sequences (976 bp) from 104 wild samples from the Xinjiang Uyghur Autonomous Region (XUAR) in north-west China, and reconstructed phylogeny with additional sequences from across the species' range. We detected 58 haplotypes in XUAR populations, all but three of which were specific to single sampling sites. The phylogenetic analysis displayed two obvious clades of mtDNA haplotypes and the other haplotypes differed from the two clades. A median-joining network showed three groups of haplotypes were to a high extent concordant with the phylogenetic tree. The haplotype clustering was consistent with their geographic distribution. Nei's net sequence divergences amongst the three groups ranged from 0.010 to 0.018 and indicated three subspecies, two of which inhabit XUAR. We detected strong differentiation between northern (NX) and southern (SX) XUAR populations overall ( F ST = 0.4448, P < 0.001), but the Mantel test showed no correlation between the genetic distance and geographic distance. Our results indicate that the NX and SX populations represent different subspecies that might be managed separately.